Water treatment plant design : (McGraw-Hill, 1998)
You can turn to the new edition of this classic reference for guidance on modernizing existing water treatment plants and planning new ones. Now with 70% new material, the Third Edition enables you to learn from 15 new chapters on environmental impact and project permitting; process residuals; construction costs; ion exchange; membrane processes; activated carbon processes; hydraulics; and more. You'll explore contributions by over 30 experts from the world's leading water quality management firms ... and keep up with the latest EPA standards and other codes.